KEBIJAKAN PENGELOLAAN LINGKUNGAN DI KABUPATEN TULUNGAGUNG DAN PIHAK-PIHAK YANG TERLIBAT DALAM PELESTARIAN LINGKUNGAN - Sanjaya, Muhammad Rama; Sulistyany, Frygyta Dwi; Mastuti, Renita Tresna; Murwani, Seftyana Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Environmental problems often arise due to inefficient management, so it is necessary to have policies that can overcome these problems. The government is expected to play a role as a policy maker who is responsible for environmental management issues. In addition, the role of the community is also important in preventing environmental problems and increasing sustainability. To examine this problem, the authors used a research methodology that included two approaches, namely a literature study and a qualitative approach to content analysis. This study found, first, that the waste generated is increasing, up to 18.3 million landfills per year. Meanwhile, the amount of waste managed was 77.28%, with a reduction of 26.73% and 50.55% of waste management. Second, the lack of good waste management, wise use needs to be done to overcome waste problems and provide direction to the community regarding the types and methods of waste management, implementation of village community service, MSME exhibitions on the results of recycling produced, if this can be implemented properly well, the waste problem itself will be minimized. Thus, continuity and inter-community conditions are important points in maximizing the realization regarding the directions given in the context of tackling waste